Optimizing Question Quality in Junior High School Exams: Classical Test Theory Evaluation with ITEMAN 4.3 - Agus Rohmatdi; Martono Martono; Zafrullah Zafrullah; Rina Safitri (STAI Hubbulwathan Duri, 2024)
This research evaluates the psychometric properties of a test using Classical Test Theory, focusing on difficulty level, discrimination power, distractor effectiveness, and reliability with ITEMAN 4.3. Researchers analyzed 149 student answers taken using Cluster Random Sampling in the Arts and Culture subject at one of the junior high schools in Sleman, Yogyakarta, Indonesia. The analysis technique used is the level of difficulty, differential power, distractor effectiveness, and reliability. From the analysis of 20 questions, it can be concluded that this test shows an almost equal level of difficulty, with 12 questions at the medium level and eight questions at the easy level. The majority of questions have excellent discrimination, with their ability to effectively differentiate between students who understand the material well and those who do not. However, there is variation in the effectiveness of distractors, with some distractors being less effective in attracting the attention of students who do not understand the material. The reliability of this test is very good, with an Alpha value of 0.892, indicating high internal consistency in measuring the same concept. This research provides a comprehensive picture of the quality of evaluation instruments used in the context of measuring student abilities.